What’s sex gotta do with it? relationship and risk factors influencing infidelity in young couples - Jefferson, Sean G. (Kansas State University, 2012)
Relationship and risk factors of infidelity within intimate and romantic relationships were examined using the Relationship and Risk factors influencing Infidelity Model (RRIM). It is based in part on Sternberg’s (1998) theoretical construct known as the triangular theory of love. Relationship factors included demographics, and relationship, development, strengths, and dynamics. Risk factors included sexual compatibility, and relationship problems. Data gleaned from Wave IV of the National Longitudinal Study of Adolescent Health (Add Health) measured a subsample of approximately 1,000 respondents (n = 939) young adults from 24 to 32 years of age (M = 28.64, SD = 1.79, Mdn = 28.61) and was designed to test the accuracy of the RRIM. Hierarchical logistic regression was used to explicate the relationships found across the elements within the RRIM. The overall results revealed that the RRIM correctly classified that 72.2% of the men and 78.8% of women were not likely to commit infidelity. The final results revealed that the level of commitment, the feeling of love, and the frequency of sex within the relationship were statistically significantly likely to influence infidelity between both men and women. Meanwhile, education and believing that one’s relationship would be permanent were statistically significantly likely to influence infidelity for women, but not for men. Although these results are encouraging, limitations were found within the RRIM and problems generated from using the Add Health must be acknowledged as several measures were not reliable. Future investigations should focus on how role models within young adults immediate and external environment influence their participation in committing infidelity.
Keywords: Infidelity; Relationships; Intimate; Risk Factors; Romantic; Young Adults; Social Psychology (0451)